Advanced financial reporting—The French approach to the disclosure problem. Issue 1 (4th June 2020) - Hecht, Andreas; Hachmeister, Dirk
Abstract: Sound decision‐making depends on an appropriate level of relevant information. This topic is on the agenda of international standard setters in order to increase the decision usefulness of financial disclosures for the addressees of corporate reporting. A look at France demonstrates how a unique recommendation on financial market communication initiated by the Financial Supervisory Authority, which goes beyond legal requirements, can help solve the problem. The resulting advanced disclosures not only provide a clear picture of the origin and magnitude of, for example, financial risks but also of the extent to which the company has reduced or increased the risk with derivative instruments. Such unprecedented transparency could raise the inhibition threshold for speculation. In addition, we illustrate that the enhanced data granularity could benefit various stakeholders through more meaningful competitive or benchmarking analyses.